The integral above is equal to , where and are coprime positive integers. Determine .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let us name the main integral as V .
V = ∫ 0 ∞ x 2 e − 2 x sin 4 x cos 2 x d x
Now, for us to be able to simplify the integral, let us make use of these two identities:
sin ( A + B ) = sin A cos B + cos A sin B sin ( A − B ) = sin A cos B − cos A sin B
Adding these two equations, we can derive such equation below:
sin A cos B = 2 sin ( A + B ) + sin ( A − B )
This changes V into
V = 2 1 ∫ 0 ∞ x 2 e − 2 x ( sin 6 x + sin 2 x ) d x
Later on we can split this into V 1 and V 2 so that the computation becomes less tedious, such that V = 2 1 ( V 1 + V 2 ) .
So now we have an integral of the form
∫ 0 ∞ x 2 e − a x sin b x d x
Let us name this integral Q , with V 1 and V 2 having the same form as Q , differing only on b .
We can do integration by parts immediately here, but to avoid such long computation, let us do this via Feynman's differentiation under the integral sign.
Let us assign (well, again) an integral I .
I = ∫ 0 ∞ e − a x sin b x d x
Differentiating this under a two times will yield the following:
I ′ = d a d ∫ 0 ∞ e − a x sin b x d x = ∫ 0 ∞ − x e − a x sin b x d x
I ′ ′ = ∫ 0 ∞ x 2 e − a x sin b x d x
Now here, we can clearly see that Q = I ′ ′ with respect to a .
So now, what is I ?
Although this integral is a lot easier to integrate than the original integral V , it will still involve a considerable amount of work. Here, we will use integration by parts twice.
I = ∫ 0 ∞ e − a x sin b x d x
let u = e − a x , and d v = sin b x d x
I = e − a x ( − b 1 cos b x ) − ∫ 0 ∞ b a e − a x cos b x d x
setting again another u = e − a x and d v = cos b x d x
I = e − a x ( − b 1 cos x ) − b a [ e − a x ( b 1 sin b x ) + ∫ 0 ∞ a 1 e − a x sin x d x ]
I = e − a x ( − b 1 cos x ) − b a [ e − a x ( b 1 sin b x ) + I ]
Further manipulation will lead us to
I = − a 2 + b 2 e − a x ( a sin b x + b cos b x ) ∣ ∣ 0 ∞
This simplifies to
I = a 2 + b 2 b
Now we have an I solved in terms of a .
Differentiating this twice, and we will get
I ′ ′ = b 2 + a 2 2 b ( 3 a 2 − b 2 )
Now, this will be the equivalent of the integral Q !
Since V takes the form of Q , we can now use the above equation to find for its value. Substituting for V 1 , with a = 2 , and b = 6 , we will have
V 1 = − 2 0 0 0 9
while V 2 on the other hand, for a = 2 and b = 2 , we have
V 2 = 1 6 1
So now we have V , and that is
2 1 ( V 1 + V 2 ) = 1 0 0 0 2 9
That now gives us 2 9 + 1 0 0 0 = 1 0 2 9